Carbonate mineral controls the transport of Cd from tailings to surrounding soils: An example from Cd-rich Niujiaotang Zn mine in Guizhou Province, Southwest China - Guo, Zidong; Gu, Shangyi; Li, Qingguang; Zhang, Tianyi; Xie, Xiaofeng; Zhao, Fengqi (Frontiers in Environmental Science, 2022)
Heavy metal pollution derived from the oxidation of sulfides in Pb-Zn mine tailings has been a common public concern. Although the oxidative dissolution of sphalerite will release cadmium into the soil environment, it is still unclear whether other minerals contain a large amount of cadmium and how much these minerals contribute to the surrounding environmental media. In this paper, XRD, particle size analyzer, SEM-EDS and improved BCR sequential extraction method were used to analyze cadmium rich zinc mine tailing and adjacent farmland soil in Duyun, Guizhou Province. The results show that the average contents of Pb, Zn, and Cd in tailing are 214 ± 71 mg/kg, 2668 ± 773 mg/kg, and 37.5 ± 9.97 mg/kg respectively. While in the surrounding soil, they were 519 ± 280 mg/kg, 3,779 ± 2614 mg/kg, and 30.8 ± 14.4 mg/kg respectively. The mineralogical composition of tailing is mainly dolomite and less pyrite. Cadmium in tailing is mainly in weak acid extractable state, indicating that cadmium mainly exists in dolomite of tailing. Pyrite in tailing generates acid through oxidation, which accelerates the dissolution of dolomite, thus releasing Cd from minerals and migrating to surrounding farmland, resulting in soil cadmium pollution. This study reveals an important process that has been neglected. Carbonate minerals play an important role in the migration of cadmium in the tailing of the Mississippi Valley-type (MVT) lead-zinc mine and the soils affected by the tailing.